Institutional and empirical essays on regulatory impact assessment - Lyons, Seán (Trinity College (Dublin, Ireland). Department of Economics, 2007)
This thesis is concerned with institutional arrangements and empirical tools that may be used to assess the impact of regulation on the economy, and thereby improve regulatory policymaking. We start in Chapter 2 with a qualitative introduction to regulatory impact assessment, highlighting some of the challenges facing small regional governments wishing to improve the quality of regulation they enact. The remainder of the thesis is divided into two parts. Part 1 considers and evaluates the optimal design of tests aimed at discovering specific classes of regulatory impact. Our particular example is a negative clearance test for the effect of regulations on competition. One such tool, the UK competition filter, has been in operation in the UK since 2002. Applying it to case studies from Ireland (in Chapter 3), we show that particular design features may easily lead to excessive false negative results. We then propose a more appropriate structure for tests of this kind. A paper based on this chapter is forthcoming in the Journal of the Statistical and Social Inquiry Society of Ireland. The analysis is extended in Chapter 4 to show that the UK filter is also prone to give excessive false negatives in its own jurisdiction; a paper drawing on these results and co-authored with my supervisor, Dr. Francis O’Toole, is under review by the Journal of Competition Law and Economics. Part 2 focuses on empirical studies of regulatory impact. Two of the three chapters in this part are concerned with aspects of mobile telephony regulation. The first of these, Chapter 5, notes that an increasing number of countries require mobile telephone networks to offer mobile number portability (MNP), which allows customers who wish to switch mobile operator to keep their mobile numbers (including the prefix) and avoid the costs of switching to new numbers. Ex ante assessments suggest that MNP should reduce switching costs and strengthen competition. We construct a new international dataset that allows us to estimate econometric models of the benefits of MNP and we test MNP’s impact on market outcomes using this international time-series cross-section data. The results show that MNP reduces average prices and encourages churn (a proxy for switching) when the switching process is rapid (e.g. less than 5 days) but not when it is slower. A paper based on the research in Chapter 5 is under review by Information Economics and Policy. Chapter 6 also employs the mobile telephony dataset introduced in Chapter 5, focusing this time on a metric popular among regulators and market analysts: average revenue per user, or ARPU. This chapter, which draws on a co-authored paper forthcoming in Telecommunications Policy, develops an econometric model of the determinants of ARPU and shows that this statistic may not be a good indicator of competitive conditions. ARPU proves to be better explained by subscribers’ incomes than by market concentration measures. In Chapter 7, we ask how far the constraints perceived and reported in surveys of small businesses (e.g. excessive regulation, access to capital) are reflected in such firms’ subsequent survival rates. There appears to be a relationship, but it is neither as strong nor as straightforward as the popularity of this sort of evidence among policymakers might lead us to expect. Indeed, the perceived barriers expected to be most significant on the basis of previous research – excessive regulation and constrained access to finance – show no significant relationship to survival rates. Until more convincing evidence is found showing that this type of survey evidence helps explain market outcomes, using it in the assessment or design of public policy may be problematical. The chapter suggests ways of enhancing surveys so that the real effects of perceived constraints can be more clearly identified. A paper drawing on it is currently under review by Small Business Economics.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin